Pengenalan Dan Pelatihan Ecoprint Untuk Meningkatkan Kreativitas Peserta Didik Smp Islam Terpadu Daar El Qur'an - Devi Lestari; Umah, Devi Nikmatul; Ramadhani, Elvara Rizka; Rini, Ajeng Setyo (Jurnal Pengabdian Kepada Masyarakat (MEDITEG), 2024)
This Ecoprint Product Introduction and Training aims to increase the knowledge and experience of Daar El Qur'an Integrated Islamic Junior High School students in the non-academic field, especially in terms of utilizing natural materials and local products. Ecoprint is one of the fashion products inspired by natural materials so it is very relevant if it is related to the issue of environmentally friendly production to encourage Indonesia's creative economy. The method used in this service is participatory by involving Daar El Qur'an Integrated Islamic Junior High School students directly through lecture and demonstration methods. Based on the results of data findings in this service, it is known that there is an increase that as many as 5% of the total number of participants have a poor level of understanding of ecoprint, 42% of participants have a fairly good understanding of ecoprint, and 53% of participants have a good level of understanding of ecoprint.